Effects of Organic Fertilizer on the Contents and Distribution of Heavy Metals in Spinach - Chuangmu, Zheng; Wei, Wu; Yukui, Rui (Asian Journal of Chemistry, 2012)
Organic fertilizer is the important source of heavy metals in vegetables. Organic fertilizer could change the availability of heavy metal in soil and concentration of heavy metals in vegetables. Eight kinds of heavy metals were determined in different organs of spinach applied different amounts of organic fertilizer to investigate the effects of organic fertilizer made from animal manure on the concentration of heavy metals in vegetables. The results showed that the organic fertilizer application can increase the contents of some heavy metals in stem and leaf of spinach, such as Cu, Zn and Se, but all heavy metals had no significant difference in stem and leaf of spinach. Root of spinach contained more Cr, Cd, Pb, Fe and Mn than stem and leaf of spinach. But application of organic fertilizer decreased the contents of heavy metals Cr, Cd, Pb, Fe and Mn, which is different from previous studies. The difference may be due to different organic fertilizer and different vegetable.